Iván Illich: hacia una desescolarización - Zúñiga Chaves, José Francisco (2003)
The aim of this article is to presente Iván Illich´s main ideas concerning his Education Philosophy. It can be said that Illich pertains to the critical thinking in Education, and breaks with all those traditional pedagogical approaches. This author criticizes the role of the teacher; the role of the school; the value of degrees etc., favoring a process of de-bureaucatization and de-schooling. He questions what the school is doing in Latin America; its ideological processes and the reduction of education to mercantile categories.